PEMANFAATAN SAMPAH ANORGANIK MENJADI ECOBRICK SEBAGAI UPAYA MENGURANGI TIMBULAN SAMPAH PLASTIK - Fajriani, Nurdani; Yusri, Hamdan; Joliastari, Febrila Ayu; Febrianti, Mila Sari; Pariarsana, I Wayan; Wathoni, Rohmatul; Putri, Yandita; Rahmatun, Dwiyani Rohlya; Oktaviana, Anisya; Karyawan, I Dewa Made Alit (Universitas Mataram, 2023)
Ecobrick as one of the innovations in managing waste generation by utilizing inorganic waste to become ecobrick products has been practiced in Semayan Village, Praya District, Central Lombok Regency, which was carried out by the 2023 University of Mataram KKN-PMD Group team. Plastic waste is the waste that dominates waste generation in Semayan Village. Various effective programs have been implemented to support the ecobrick program to be inclusive in the Semayan Village area. The realization of this program touches various layers of society, starting from the age of the children. The program is aimed at TPQ children in several neighborhoods and 2 elementary schools. Many teenagers also participate in making ecobricks. Then the demonstration of making ecobrick was also aimed at ladies and gentlemen. With the participation of all levels, it is possible for this ecobrick program to run smoothly, to have a good and sustainable impact on Semayan Village. The presence of this ecobrick innovation is a creative step that is useful for the Semayan Village community, be it reducing plastic waste, increasing community creativity, even this innovation can improve the economy of the surrounding community. This paper aims to provide knowledge to readers regarding one way to manage inorganic waste.